Pengaruh Live Streaming, Content Marketing dan Online Customer Review terhadap Keputusan Pembelian pada Tiktok Shop di Banda Aceh - Nadia Sharfina; Amelia Amelia; Nadiya Nadiya (Pusat Riset dan Inovasi Nasional, 2026)
The development of digital technology has encouraged an increase in online shopping activities in Indonesia, including through the TikTok Shop platform which combines social media features and e-commerce transactions in one ecosystem. Although the platform is experiencing rapid user growth, the low buying interest of some consumers indicates a weakness in the digital marketing strategy implemented. Therefore, this study aims to analyze the influence of live streaming, content marketing, and online customer reviews on purchase decisions among TikTok Shop users in Banda Aceh. This study uses a quantitative approach through a survey of 96 respondents with purposive sampling technique. The data were analyzed using multiple linear regression to test the simultaneous and partial influences between the variables studied. The results of the study show that the three variables simultaneously have a significant effect on purchasing decisions. Partially, content marketing and online customer reviews have been shown to have a significant influence, while live streaming does not show a significant influence. These findings underscore the importance of informative content-based marketing strategies and customer review management to strengthen trust and increase consumer buying interest on social-commercial platforms such as TikTok Shop.